WDM-RoF Architecture for Low-Cost and Large-Coverage 5G Applications - Mohammed, Safa; Desher, Ismael (Engineering, Technology & Applied Science Research, 2025)
This paper presents an enhanced Wavelength Division Multiplexing (WDM) method based on the Radio over Fiber (RoF) architecture to achieve cost-effective, long-distance, and high-coverage communication for 5G systems. The proposed model addresses the critical challenges of increasing the number of channels and transmitting the Radio Frequency (RF) signal along 72 km distance while ensuring enhanced data rates and reduced latency across extensive coverage areas. Performance evaluations demonstrate that the 8-channel model (80 Gbps) has quality factors of 6.8, 7.5, 7.8, and 7.7, and the minimal Bit Error Rate (BER) is 2.9E-10, 2.2E-11, 2.2E-12, and 4.2E-12. The 16-channel model (160 Gbps) has quality factors of 5.6, 6.5, 6.8, and 6.9 with minimal BERs of 2.9E-8, 2.2E-10, 2.2E-10, and 4.2E-11, respectively. The 32-channel model (320 Gbps) has quality factors of 5.4, 6.1, 6.3, and 6.2 with minimal BERs of 2.9E-8, 2.2E-11, 2.2E-10, and 4.2E-10. The results highlight the potential of the proposed Wavelength Division Multiplexing Radio over Fiber (WDM-RoF) model to serve as a robust backbone for next-generation mobile networks, meeting the demands of 5G communication.